Effect of temperature on the speed of coffee roasting - Porras-Zúñiga, María Cristina (2019)
The roasting process produce some important changes in physical, chemical and sensory properties of coffee. The production of roasting coffee is related with the temperature of the toaster, the time and the quantity. Temperature is the less studied parameter; however, it has an important potential to associate it with physical and chemical changes. The objective of the investigation is to establish the effect of temperature of roasting in the speed of roasting of grains. They were used coffee grains (Coffea arábica) from Zona de Los Santos, with 80 points of sensory analysis, using a horizontal rotary cylinder. They were set three positions of the gas valve to have different conditions of the operation of roasting. They were used five samples of 600 g for every condition of roasting. The final roasting was determinate with the temperature of 215, 220, 225, 230 and 235 °C. The increase of temperature in those conditions was linear with a coefficient of determination higher than 93% and the slope represent the speed of internal air heating. The speed of heating was related with the balance temperature of the toaster through the Arrhenius Model. They were determinate the activation energy to the heating system: 21.6 kJ/mol. The increase of gas consumption generates a higher speed in the heating of toaster, grains and the air.